La tutoría como dispositivo de enseñanza - Colmegna, Pablo (2020)
The instant work proposes the implementation of a mentoring system for the law courses at the School of Law of the University of Buenos Aires (FDUBA), in order to adjust teaching processes to the different contexts that students go through, in the light of a more humane teaching perspective and aimed at training future lawyers with a social profile. The proposal arises as a result of the need to adapt to distance teaching and learning due to the COVID-19 pandemic, which reinforced (or should have reinforced) the professors' presence in monitoring student learning. Hence, the proposed strategies emphasize the need to innovate as regards teaching devices, their scientific and pedagogical relevance, the approach to tutorials and their institutional plausibility at the FDUBA, their advantages as promoters of skills and abilities, as well as the obstacles to their implementation. In conclusion, we present a project that, through flexibility and empathy, aims at improving and enhancing educational quality and at increasing retention rates.